A systematic review of teacher roles and competences for teaching synchronously online through videoconferencing technology. (November 2022) - Grammens, Maaike; Voet, Michiel; Vanderlinde, Ruben; Declercq, Lieselot; De Wever, Bram
Abstract: As a growing number of educational institutions are offering online programs, teachers need to be competent in this new way of teaching. This is especially the case for synchronous online learning through videoconferencing technology, an emergent and so far understudied form of online education. Based on a systematic literature review of 30 studies, this study identifies 24 competence clusters, which can be grouped into 5 teacher roles associated with synchronous online teaching through videoconferencing: the instructional, managerial, technical, communicational, and social role. This framework can act as a starting point for future research on this understudied topic and can also provide directions to support teachers' professionalization and practice. Highlights: The systematic literature review shows that synchronous online teaching through videoconferencing requires specific competences. We present a framework for clarifying teachers' roles and competences that are required for synchronous online teaching. The research synthesis offers directions for professional development initiatives and for teachers to optimize their teaching.